Noam Chomsky: His vision of Colombia - Villarreal, Neyla Johana (Rastros Rostros, 2011)
This article is an approach to life and work of the notorious thinker Noam Chomsky. We offer this section of great biographies to Noam Chomsky because of the political role he represents and which is in coherence with the dossier of this publication. The development of Transformational Generative Grammar is his first major contribution to the development of linguistic science and thought of the twentieth century. His vision about U.S. relations with Latin American countries and particularly with Colombia is the second part of this article. This work is possible by some interviews given to the Colombian Media.